Biomechanical report for the IAAF World Championships London 2017 110 m hurdles men's - Pollitt, L.; Walker, J.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
Olympic champion Omar McLeod withstood the pressure to open the Jamaican gold medal account at the World Championships with victory in a time of 13.04 s. Coming into the event with an impressive world lead (12.90 s) and off the back of an assured semi-final performance (13.10 s), McLeod held off the challenge of defending champion Sergey Shubenkov. Shubenkov had a huge challenge just to make the final after being drawn in the ninth lane in his semi-final and despite being drawn in lane 2 away from the action in the final, he secured silver in 13.14 s one tenth behind McLeod. It was a highly technical performance from Shubenkov as he did not disturb any of his ten hurdles. Hungary`s Balazs Baji claimed Hungary`s first ever track medal, to capture the bronze. The only other athlete to clear all ten hurdles without disturbing them was 2012 Olympic champion and world record holder Aries Merritt; who, less than two years after undergoing kidney transplant surgery, finished fifth in a time of 13.31 s. The men`s final could have been a more closely contested affair if Garfield Darien of France had produced a stronger technical performance. He hit all of the first four hurdles, knocking three completely over. Despite still being in medal contention by the hurdle seven, he knocked over the final three hurdles and was overtaken by Baji on the run-in to the line. (Attention! registration on the IAAF site is required for downloading)